Adult-Onset Woakes’ Syndrome: Report of a Rare Case - U. Schoenenberger; A. J. Tasman (Case Reports in Otolaryngology)
Introduction. Woakes’ syndrome, commonly defined as severe recurrent nasal polyps with consecutive destruction of the nasal pyramid, is rare with only a few reports in the literature documenting surgical treatment of the external nose. Case Presentation. We describe the case of an adult patient with Samter’s triad who had been surgically treated from nasal polyposis since 2002. By 2014 a conspicuous deformity of the nasal pyramid had progressively occurred due to a recurrence. The patient underwent revision endoscopic sinus surgery and narrowing of the bony nasal vault by digital compression without osteotomies. Discussion. Having been described over 130 years ago, the etiology of Woakes’ syndrome remains poorly understood. Treatment includes endoscopic sinus surgery and topical treatment. Surgical treatment of the external nose deformity by rhinoplasty is rarely addressed. Conclusion. This case illustrates that the widening of the bony nasal vault may be successfully corrected by digital compression, if the nasal bones are substantially thinned, in combination with surgical treatment of nasal polyps.